Drosophila uses a tripod gait across all walking speeds, and the geometry of the tripod is important for speed control - Chun, Chanwoo (eLife, 2021)
Changes in walking speed are characterized by changes in both the animal’s gait and the mechanics of its interaction with the ground. Here we study these changes in walking Drosophila. We measured the fly’s center of mass movement with high spatial resolution and the position of its footprints. Flies predominantly employ a modified tripod gait that only changes marginally with speed. The mechanics of a tripod gait can be approximated with a simple model – angular and radial spring-loaded inverted pendulum (ARSLIP) – which is characterized by two springs of an effective leg that become stiffer as the speed increases. Surprisingly, the change in the stiffness of the spring is mediated by the change in tripod shape rather than a change in stiffness of individual legs. The effect of tripod shape on mechanics can also explain the large variation in kinematics among insects, and ARSLIP can model these variations.